Pengaruh Sikap, Lingkungan, dan Kesadaran Wajib Pajak terhadap Kepatuhan Wajib Pajak: (Studi Pada Wajib Pajak Orang Pribadi dan Badan di KPP Pratama Sukoharjo) - Mahendra Bayu Sata (Media Ilmiah Akuntansi, 2021)
The aim of this study was to determine the effect of Attitude, Environment, and Tax Awareness on Tax Compliance at Sukoharjo Tax office. Population on this study were All Registered Taxpayers at Sukoharjo Tax office. The study was conducted during 2021. Sampling used random selection, especially for taxpayers who have a large tax risk or potential, number of samples determined was 10 registered taxpayers at Sukoharjo Tax Office until 2021. The Data source in this study used to primary data obtained from The informants by means of interviews and observations and secondary data, collected via documents and evidence from Sukoharjo Tax Office. The data analysis technique used qualitative descriptive analysis research method with The Constant Comparison Method. The results of this study indicate lest The taxpayer’s attitude, the environment of taxpayers, and the awareness of the taxpayers at Sukoharjo tax office have an effect on tax compliance in addition to other factors such as: the condition of the state Tax Administration System, Services for Taxpayers, Tax Law Implementation, Tax Audit, and Tax Rate. Although not all taxpayers feel the effect.